The Convergence of Hyperautomation and Autonomous Remediation: Mitigating Site Reliability Engineering Toil in Cloud-Native Ecosystems (Emerging Indexing of Global Multidisciplinary Journal, 2026)
The rapid evolution of cloud-native architectures has necessitated a fundamental shift in operational paradigms, moving away from manual intervention toward a sophisticated state of autonomous self-healing. This research explores the intersection of Site Reliability Engineering (SRE), hyperautomation, and Artificial Intelligence (AI) to address the persistent challenge of "toil"-repetitive, manual tasks that hinder scalability and contribute to professional burnout. By synthesizing current advancements in AI-driven fault prediction, automated incident response, and predictive analytics for multi-cloud environments, this paper proposes a holistic framework for safe autonomous remediation. The study investigates how modern organizations can transition from traditional DevOps practices to advanced SRE strategies that leverage machine learning for root cause analysis and proactive system stabilization. Special attention is given to the psychological and organizational impacts of toil, the technical requirements for self-healing Enterprise Resource Planning (ERP) systems, and the role of CI/CD automation in financial and technical data validation. The findings suggest that while the transition to fully autonomous systems presents significant technical and security challenges, the integration of predictive engines and automated remediation protocols is essential for the long-term reliability and sustainability of complex, high-scale software environments.